Strategy on The Effectiveness of Learning Outcomes of Manufacturing Calculus Using Edlink in The Covid-19 Pandemic (EduMa: Mathematics education learning and teaching, 2021)
The Covid-19 pandemic in Indonesia has resulted in a change in the learning implementation system at IKIP Muhammadiyah Maumere, carried out face-to-face. Even so, the EdLink platform's presence in the learning system at IKIP Muhammadiyah Maumere can be a solution by providing easy online learning offers for lecturers and students. Therefore, this study aims to analyze the strategies for learning achievement effectiveness during the pandemic in the variable calculus course using the EdLink platform. This research uses qualitative descriptive data, with the target of testing is mathematics education students in semester 5 and semester 7 with a total of 29 students. The research scale used is the percentage score of the effectiveness of learning outcomes. The assessment scale uses an item scale with a score of 0-100 to assess students towards lecturers. Whereas the student questionnaire used a Likert scale with a score of 1-4. The results showed that the students enthusiastically joined the variable calculus class using the EdLink application. The results showed that for student learning outcomes and the assessment questionnaire results, EdLink was effectively applied during the Covid-19 pandemic.Â